Load-Balancing using HA Proxy on Multipath System with Flow Slice - Radha, Pallavali; Surekha, C; Sesadri, U (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
To provide switching capacity in terabit or petabit uses core routers in multipath switching systems (MPS). Without disturbing the order of intra flow packets, the load balance across multiple paths is the main issue of MPS design phase. The performance is not good through heavy tailed flow size distribution in flow based hashing algorithm. Our proposed novel scheme consist the HA Proxy very fast and reliable solution offering high availability, load balancing, and proxying for TCP and HTTP-based applications. To process Layer7 of web site or to provide persistence to the website this scheme is very well suited for heavy load web sites crawling and flow slices are generated through Flow Slice (FS) that halt each flow at every intra flow spell larger than a slicing threshold and balances the load. The study analysis on traces of Internet, our scheme is optimal in load balancing performance through FS and the slicing threshold we set to 1 to 4 ms. We neglected out of order packets limits of probability 1/106 on three prominent MPSs with little hardware complexity and twice of the internal speedup. The theoretical analysis proved that this and trace driven prototype simulations are validated. Â 